The effect of altering strength and approach velocity on triple jump performance - Allen, S.; King, M.; Yeadon, F. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The triple jump is an athletic event comprising three phases in which the optimal proportion of each phase to the total distance jumped, termed the phase ratio, is unknown. This study used a whole body torque-driven computer simulation model of all three phases of the triple jump to investigate the effect of strength and approach velocity on optimal technique. The strength and approach velocity of the simulation model was increased by up to 30% in 10% increments from baseline data collected from a national standard triple jumper. Increasing strength always resulted in an improved performance, increasing velocity also typically resulted in an improved performance but there was a point past which increasing velocity without increasing strength did not lead to an increase in performance. Increasing both strength and velocity by 10%, 20%, and 30% led to roughly equivalent increases in triple jump distance. The phase ratio employed by the simulation model typically became more balanced when the strength of the model was increased by more than its velocity.